2010
DOI: 10.1021/la100638u
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Zinc Porphyrin Complexes on Pyridine-Functionalized Glass Surfaces

Abstract: In order to immobilize sublimable and fluorescent dye molecules on transparent surfaces for the detection of far field molecular interference experiments, we investigate the potential of pyridine-functionalized glass substrates as coordination sites for the zinc complex of tetraphenylporphyrin (ZnTPP). Borosilicate glass is functionalized with 4-(6-(ethoxydimethylsilyl)hexyloxy)pyridine in order to cover the glass surface with pyridine subunits. ZnTPP molecules are deposited by sublimation through mechanical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Indeed, previous reports suggest that ZnTPP presents strong affinity to pyridine, thiol and trithiocarbonate. 108 To clarify this finding, we have performed UV−visible spectroscopy of ZnTPP, ZnTPP/BTPA (SI, Figure S1) and ZnTPP/CPADB (SI, Figure S1) before and after light irradiation. In the presence of BTPA and ZnTPP, we observed a new signal at 620 nm, while the signals of ZnTPP/CPADB did not change.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous reports suggest that ZnTPP presents strong affinity to pyridine, thiol and trithiocarbonate. 108 To clarify this finding, we have performed UV−visible spectroscopy of ZnTPP, ZnTPP/BTPA (SI, Figure S1) and ZnTPP/CPADB (SI, Figure S1) before and after light irradiation. In the presence of BTPA and ZnTPP, we observed a new signal at 620 nm, while the signals of ZnTPP/CPADB did not change.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The discrepancy in the polymerization rates can be attributed to the coordination of zinc to the thiocarbonylthio moiety on RAFT which may lead to higher efficiency of PET-RAFT activation. Indeed, previous reports suggest that ZnTPP presents strong affinity to pyridine, thiol and trithiocarbonate . To clarify this finding, we have performed UV–visible spectroscopy of ZnTPP, ZnTPP/BTPA (SI, Figure S1) and ZnTPP/CPADB (SI, Figure S1) before and after light irradiation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, it has been reported that zinc has a strong coordination for thiocarbonylthio moiety on RAFT agent and can promote the occurrence of PET‐RAFT polymerization. [ 20 ] This proves that the high‐efficiency synergy of perovskite and PCN‐222 can enhance the photocatalytic polymerization performance of the photocatalyst far beyond the role of TCPP and TCPP‐metallazed catalysts.…”
Section: Resultsmentioning
confidence: 90%
“…However, in this polymerization system, the results were reversed due to the addition of Zn­(TCPP), indicating that there is a special recognition mechanism between CDTPA and Zn­(TCPP). Previous studies reported that Zn­(TCPP) has a strong affinity for pyridines, thiols, and trithiocarbonates, thus leading to zinc coordination to the thiocarbonylthio groups on the RAFT chain transfer agent, which may be the reason for the obvious activation efficiency of CDTPA in Zn­(TCPP)-mediated PET-RAFT. To test this guess, UV–vis spectroscopic analysis of Zn­(TCPP) (curve c, Figure S1), Zn­(TCPP)/CDTPA (curve a, Figure S1) and Zn­(TCPP)/CPAD (curve b, Figure S1) were performed under illumination.…”
Section: Resultsmentioning
confidence: 99%